Incidence and risk factors for incisional hernia and recurrence: Retrospective analysis of the French national database. (5th April 2021) - Gignoux, Benoit; Bayon, Yves; Martin, Damien; Phan, Raksmey; Augusto, Vincent; Darnis, Benjamin; Sarazin, Marianne
Abstract: Aim: The aim of this work was to determine the rate of incisional hernia (IH) repair and risk factors for IH repair after laparotomy. Method: This population‐based study used data extracted from the French Programme de Médicalisation des Systèmes d'Informations (PMSI) database. All patients who had undergone a laparotomy in 2010, their hospital visits from 2010 to 2015 and patients who underwent a first IH repair in 2013 were included. Previously identified risk factors included age, gender, high blood pressure (HBP), obesity, diabetes and chronic obstructive pulmonary disease (COPD). Results: Among the 431 619 patients who underwent a laparotomy in 2010, 5% underwent IH repair between 2010 and 2015. A high‐risk list of the most frequent surgical procedures (>100) with a significant risk of IH repair (>10% at 5 years) was established and included 71 863 patients (17%; 65 procedures). The overall IH repair rate from this list was 17%. Gastrointestinal (GI) surgery represented 89% of procedures, with the majority of patients (72%) undergoing lower GI tract surgery. The IH repair rate was 56% at 1 year and 79% at 2 years. Risk factors for IH repair included obesity (31% vs 15% without obesity, p < 0.001), COPD (20% vs 16% without COPD), HBP (19% vs 15% without HBP) and diabetes (19% vs 16% without diabetes). Obesity was the main risk factor for recurrence after IH repair (19% vs 13%, p < 0.001). Conclusion: From the PMSI database, the real rate of IH repair after laparotomy was 5%, increasing to 17% after digestive surgery. Obesity was the main risk factor, with an IH repair rate of 31% after digestive surgery. Because of the important medico‐economic consequences, prevention of IH after laparotomy in high‐risk patients should be considered.